Effects of L-Arginine, Vitamin E and Their Combinations on Sperms Morphology in Albino Male Mice - Husein, Raza H; Ahmed, Mahmood O; Muhammed, Sulaf M (Al-Nahrain Journal of Science, 2011)
This study designed to evaluate the effected of L-arginine, vitamin E and their combinations on sperms morphology (sperm quality). Twenty (20) male albino mice was included in this study and dividing into four groups (Control group, Vitamin E treated group, L-arginine treated group, and Vitamin E+ L-arginine treated Group). The animals were kept under suitable conditions of temperature (24±2 ْ C) and light program (12-14 hours/ day). Results revealed that mice treated with vitamin E + L-arginine (0.80 ± 0.141) showed a significant (p≤0.05) decrease in numbers of abnormal sperm without head, treatment mice with vitamin E + L-arginine (1.68 ± 0.10) gave a significant decreased in numbers of abnormal sperms without tail, mice treated with vitamin E (1.00 ± 0.38) and (L-arginine + vitamin E) (0.52 ± 0.14) significantly decreased sperms without hook, furthermore mice treated with vitamin E (11.04+1.63) significantly decreased sperms defective head when compared with control groups. the period of experiments were 30 days. The percentages of abnormal sperm morphology were calculated by counting 200 spermatozoa.